The inter-relationships between regulation and competition enforcement in the South African liquid fuels industry - Nair, Reena Das; Mondliwa, Pamela; Roberts, Simon (Journal of Energy in Southern Africa, 2015)
The competition authorities have devoted considerable time and energy to investigating anticompetitive conduct in the broad area of liquid fuel, gas and related products, where regulation sets rules for firm conduct. Competition cases have included the Sasol-Engen merger, collusive arrangements in gas distribution and the pricing of bitumen for road construction projects, and alleged coordination through information exchange in diesel. Drawing on a review of these matters we assess the inter-relationships between regulation and competition enforcement. We argue that regulation can be designed to enable greater competitive rivalry, while anti-competitive conduct can also be better remedied through recognition of the role of regulation.